Kesiapan & Efektivitas TER PPh 21 dalam Administrasi Pajak pada Perusahaan Dagang di Palembang - Fidel Rizky Caesar; Usnia Wati Keristin (MDP Student Conference, 2026)
This study examines company readiness and the effectiveness of implementing the Average Effective Rate (TER) for Income Tax Article 21 in tax administration at trading companies in Palembang City. The purpose of this study was to determine company readiness and assess the effectiveness of the Average Effective Rate (TER) in tax administration at trading companies. The approach used in this study was quantitative. The study population included all trading companies operating in Palembang City, while the sample size was determined using the Slovin formula. Primary data were collected through questionnaires. Data processing and analysis were performed using the SmartPLS 4 application. The analysis results showed that readiness and effectiveness had a positive and significant impact, with t-statistics of 3.279 and 6.640, and p-values ​​of 0.001 and 0.000, respectively.